Analisis Sistem Pelayanan Pendaftaran Online Poliklinik Jantung di Rumah Sakit Umum Pusat Dr. Sardjito Yogyakarta - Ita Roossinta; Yunita Widiyati Nikmah; M. Fakhry Asa Fazary (Pascasarjana Universitas Jember, 2022)
Simulation is widely used to model a system that is already running which is then attempted to be repaired or increased its utility. One of the averages reaches 1 hour, especially for the queue of patients who will have an examination with a specialist. The simulation results give different results from the actual conditions. This difference in conditions is caused by several factors, including data limitations, a problem that is often solved using a simulation approach is the queuing system. This study uses the object of patient queues at the Cardiology Polyclinic, Dr. Sardjito as a case study. In actual conditions, patient waiting time and some managerial problems such as the arrival of doctors and service hours that are not on time.